Grounding Twenty-first-Century Public Relations Praxis in Aristotelian Ethos - Ofori, D.M. (JOURNAL OF PUBLIC RELATIONS RESEARCH, 2019)
By grounding public relations praxis in Aristotelian ethos, practitioners can function as liaison officers with balanced perspectives, capable of co creating meaning with both client organizations and their publics between whom experts are hired to facilitate mutually beneficial relationships. This approach locates persuasion at the nexus of speaker ethos in the public relations process. It allows practitioners to balance their commitment to the ethics of their profession with loyalty to clients, while empowering audi ences (organizations and their publics) to function as the final arbiters of any courses of action proposed to them. Moreover, because the approach enables practitioners, based on their credible ethos, to participate in orga nizational decision-making, it has the potential to transfer their ethical worldview to client organizations. Ultimately, the central theoretical con tribution of this essay is an alternative approach to public relations praxis founded on an analysis of Aristotle’s notion of phronesis, arête, and eunoia.
Research Article
Keywords: Aristotle; ethos; phronesis